The Function of Timorese Gong Music in The Tfua Ton Ritual Ceremony in Napan Kefamenanu Village - Renaldus Afoan Elu, Agustinus; Utomo, Udi; Sunarto, Sunarto (Universitas Negeri Semarang, 2019)
Tfua Ton is a ritual ceremony carried out by the community in Napan Village to ask for rain and soil fertility to Uis Neno (God) and Uis Pah (deceased ancestors). In the ritual there is a Timorese Gong instrument that has an important role in it. The gong consists of Tonu mese, Ote and Kbola and one drum (Ke'e). The purpose of this study is to analyze the function of the Timorese Gong Music in the Tfua Ton Ritual Ceremony. The method used in this study is qualitative interpretive with phenomenological approach. Data collection techniques with observation, interview and document study techniques. Check the validity of the data by using data triangulation, researcher’s triangulation, triangulation of theories, methods and techniques. For data analysis, the researchers used the theory of music function from Allan P. Merriam with stages of data reduction, data presentation, and conclusion (verification). The results of the study are Timorese Gong in the Tfua Ton ritual have an important role in it and have become a part of traditional rituals. Timorese Gong In the Tfua Ton ritual has several functions, including functioning as aesthetic appreciation, as entertainment, as an emotional expression, as communication and education, integrating society, as an endorsement of social institutions and religious rituals. Timorese Gong can function to show the existence, character and identity of the Dawan people in Napan Village. The results of this study can provide understanding and increase knowledge to the people of Napan Village and the younger generation to better understand Timorese Gong music in the Tfua Ton ritual, besides it is expected that the Napan Village community will continue to preserve and maintain Timorese Gong music as one of the traditional music of the society.